J. Hasselaar. Medical and ethical aspects of palliative sedation practice in the Netherlands. From controversy to guideline and beyond. - Janssens, Rien; Hasselaar, Jeroen (Tijdschrift voor Gerontologie en Geriatrie, 2010)
bespreking proefschrif J. Hasselaar. Medical and ethical aspects of palliative sedation practice in the Netherlands. From controversy to guideline and beyond.